Enkapsulasi Propagul Jamur Entomopatogen Beauveria bassiana Menggunakan Alginat dan Pati Jagung sebagai Produk Mikoinsektisida - PRIYO WAHYUDI (Fakultas Farmasi Universitas Pancasila, 2008)
Negative effects of chemical pesticides experienced by farmers have encouraged researchers to develop bioinsectiscide. Beauveria bassiana is one of entomopatogen fungus that may be used as an active compound of mycoinsecticide. The main constraint of this mycoinsecticide is retaining the viability of Beauveria bassiana propagules. The encapsulation of active propagule of Beauveria bassiana using sodium alginate and corn starch was studied in this experiment. The aim is to get the formula of mycoinsecticide with a high viable propagules contain for long storage period. Liquid fermentation were proceed to produce active biomass of Beauveria bassiana, followed by encapsulation using sodium alginate (Formula I) and corn starch (Formula II). After encapsulation and the 1st, 2nd, and 3th Week of storage in room temperature, viability test was carried out. The result showed that Formula I and II were able to immobilize effectively, but the number of viable propagule was slightly reduced. The number of viable propagule of Beauveria bassiana in Formula I and ll after three Weeks storage was 8.75 x 106 cfu/g and 6.13 x 106 cfu/g respectively. It can be concluded that encapsulation using sodium alginate and corn starch could retain propagule of Beauveria bassiana in viable number.